« A Whore entring into prison is a Hony-pot ». Les geôles au féminin (xvie-xviiie siècles) - Natalia Muchnik (Criminocorpus)
The prison world today is clearly gendered: women represent only a small minority of prison guards and inmates (about 4% in France). This was clearly not the case in the 16th-18th centuries. Not only were the spaces of confinement usually mixed, but women made up a significant proportion of the prisoners. While prostitution and theft were some of the dominant reasons for incarceration, the charges were in fact much more diverse. The female presence is also embodied in the multitude of people who gravitate in and around the prison. This omnipresence, the containment of which marks the beginnings of prison reforms from the 17th century onwards, is one of the specificities of the period. It is precisely the place of women and the measures it gives rise to that this contribution proposes to examine in France, England and Spain.